Massive ascitis secondary to severe preeclampsia: case report - Tutal Muñoz, Luis Miguel (2022)
Preeclampsia is a pathology with multiple implications and a cause of maternal and perinatal morbidity and mortality. Although its frequency is low, ascites is a clinical sign to be taken into account. We report the case of a 33.1-week pregnant woman with severe preeclampsia, in whom ascites was observed during cesarean section and evolved to massive ascites on the second postoperative day, requiring invasive management (pig tail drainage) and transfer to the ICU for 6 days. She needed nitroprusside for 2 days due to persistent hypertensive crisis, with progressive improvement and discharge from the clinic after 12 days.